Telomeric RNA quadruplexes as targets for cancer prevention: The therapeutic potential of agonodepsides - Gourav Choudhir; Sushil Kumar; Mohammad Shahid; Anas Shamsi; Asimul Islam (Journal of Genetic Engineering and Biotechnology)
Background: Cancer remains an awful challenge, despite years of targeting proteins to control its relentless growth and spread. Fungal metabolites, a treasure of natural chemicals, offer a glimmer of hope. Telomeres, the cellular “caps,” are a focal point in cancer research. This study explores the potential of stabilizing Telomeric Repeats-containing RNA G-quadruplex (TERRA G4) structures within telomeres. This stabilization could block telomerase, the enzyme that repairs telomeres, and potentially trigger cancer cell death. Agonodepsides A and B, two promising fungal metabolites, were chosen to investigate this exciting possibility. Methods: Agonodepside A and B were initially screened for drug likeness employing SwissAdme. AutoDock Vina was used for molecular docking, and ligands and TERRA G4 were prepared using PyRx and MGL tool. Discovery Studio software was utilized for the visualization of interactions between ligands and TERRA G4. For validation of docking results MD simulation for control and complexes was carried out for 250 ns and trajectories were analyzed for different parameters. MMPBSA was used to calculate binding free energy for control and complexes. To find the stable and lower energy states of complexes in comparison to control principal component analysis (PCA) and free energy landscape (FEL) were conducted. Results: Absorption, distribution, metabolism, and excretion (ADME) of both agonodepsides followed Lipinski’s rule of five with zero violation. Molecular docking revealed several key interactions including hydrogen bonds, van der Waals interactions, π-alkyl and π-anion. MD simulation revealed that Agonodepside A interact with TERRA G4 and stabilize it while Agonodepside B interactions were transient. The MMPBSA binding free energy calculation, PCA and free energy landscapes supported the docking and MD simulation results. Conclusion: Lichenized fungi produce agonodepsides A and B, may fight cancer by targeting telomeres. Agonodepside A binds more strongly to telomeres than B, potentially blocking enzyme telomerase. Further studies are required to validate these findings and evaluate potential safety concerns.